Influence of crop rotation and tillage systems on soil properties and productivity of soybean (Glycine max (L.) Merrill) and wheat (Triticum aestivum) in Malwa region of Central India - Vyas, A.K.; Meena, Hariom; Ramesh, A.; Billore, S.D.; Pandya, N.; Khan, I.R. (Annals of Agricultural Research, 2014)
Soil physical, chemical and biochemical properties and productivity of soybean and wheat in Malwa region of Central India were studied under a long-term field trial involving four soybean based crop rotations (soybean-wheat, soybean-wheat-maize-wheat, soybean-wheat-soybean-wheat-maize- wheat and soybean+maize-wheat) and three tillage systems (conventional-conventional, conventional-reduced and reduced-reduced) being continuously maintained since, 2001. After completing six cropping seasons, the reduced-reduced (R-R) tillage system considerably increased the bulk density, porosity and water filled pore space (WFPS) at wheat harvest during 2007-08. The R-R and conventional-reduced (C-R) tillage systems had significantly higher available P and K content in the surface soil. The R-R tillage system significantly increased soil organic carbon (SOC), particulate organic carbon (POC) and light fraction carbon (LFC) contents as compared to C-C and C-R systems. On mean basis, maximum soybean yield was obtained in C-C tillage system (2.13 t/ha) which was 1.4 and 6.5% higher over C-R and R-R systems, respectively while, wheat grain yield under C-C tillage system was higher to the tune of 2.2 and 5.1% over C-R and R-R system. There was no significant influence of crop rotation on bulk density, porosity and WFPS at wheat harvest during 2007-08. Inclusion of maize in the crop rotation increased the available P and K content in the soil. The crop rotations viz. S-W-M-W and S-W-S-W-M-W had higher SOC, POC and LFC contents as compared to S-W rotation. On mean basis, maximum soybean seed yield (2.54 t/ha) was recorded in S+M-W rotation which was higher to the tune of 21.5, 39.6 and 36.6 % over S-W, S- W-M-W and S-W-S-W-M-W rotations, respectively. Crop rotations did not show considerable effect on wheat grain yield.